Computational Study of Electromagnetic Fields, Eddy Currents and Induction Heating in Thin and Thick Workpieces (Communications in Computational Physics, 2010)
A set of 2D steady state finite element numerical simulations of electromagneticfields, eddy currents distribution and induction heating pattern has been done fordifferent thicknesses of a metal workpiece. Comparison between the calculation resultsshow the importance of workpiece thickness on induction heating process includingelectromagnetic field distribution, eddy currents pattern, heating structure and coilefficiency.